2015
DOI: 10.5198/jtlu.2015.406
|View full text |Cite
|
Sign up to set email alerts
|

Large urban freight traffic generators: Opportunities for city logistics initiatives

Abstract: This paper develops procedures to identify and quantify the role played by large urban freight traffic generators as contributors of truck traffic in metropolitan areas. Although ports, container terminals, and other industrial sites are usually associated with large generations of truck trips, they only represent a small proportion of the total trips produced and attracted in large metropolitan areas. This paper analyzes the importance of other facilities such as ordinary businesses or buildings that individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…Based on the average number of truck trips per business observed during our data collection, we estimated 37,500 truck trips generated daily by these malls, an average of 330 truck trips per mall. This number is not too far from other estimates found in the literature; for instance Jaller et al [1] found that the Grand Central Station of New York hosts 184 businesses and attracts 100 to 250 trucks per day. Eidhammer et al (2016) [29] reports an average of 5.1 shipments per week generated by a retail located in a shopping mall, and compared it with an average of 4.7 shipments/week for a retail store located on-street.…”
Section: Motivation and Research Focuscontrasting
confidence: 40%
See 3 more Smart Citations
“…Based on the average number of truck trips per business observed during our data collection, we estimated 37,500 truck trips generated daily by these malls, an average of 330 truck trips per mall. This number is not too far from other estimates found in the literature; for instance Jaller et al [1] found that the Grand Central Station of New York hosts 184 businesses and attracts 100 to 250 trucks per day. Eidhammer et al (2016) [29] reports an average of 5.1 shipments per week generated by a retail located in a shopping mall, and compared it with an average of 4.7 shipments/week for a retail store located on-street.…”
Section: Motivation and Research Focuscontrasting
confidence: 40%
“…Although this initiative is relatively unexplored, it could reduce parking congestion since (1) it reduces the parking durations, and therefore increase the parking turnover at the loading bay and (2) it gives vehicles' drivers more freedom in choosing the arrival time and in scheduling their deliveries. However, to be effective, we recommend that such centralized receiving stations should (1) operate off-peak and outside the store opening times and (2) should be able to handle pick-ups, namely retrieving the goods from the stores and staging them at the loading bay until the drivers arrive at the mall.…”
Section: Managerial Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most towers do not cover a large footprint, the various businesses in these towers collectively generate more freight movements as compared to on-street retailers and the businesses located within a single city block [27]. For instance, freight deliveries to businesses located within 56 neighbouring buildings in Manhattan, New York, accounted for about 4% of the total truck movements in all of Manhattan, which encompasses thousands of other buildings and business establishments [28]. In addition, businesses in commercial towers receive a large volume of express mail deliveries.…”
Section: Overview Of Last Mile Delivery Activities To Retailers and Bmentioning
confidence: 99%